Dissimilarity in physical attractiveness within romantic dyads and mate retention behaviors. (June 2017) - Oltmanns, Joshua R.; Markey, Patrick M.; French, Juliana E.
The present study investigated the relations among physical attractiveness and inter- and intrasexual mate retention tactics used by individuals in romantic relationships. Seventy-three undergraduate romantic dyads were photographed and completed a questionnaire about their mate retention tactics. Independent judges rated the photographs for physical attractiveness. Actor–partner interdependence models indicated that (a) partner's physical attractiveness was positively associated with the individual's own use of mate retention behavior, (b) an individual's own level of physical attractiveness was not related to the individual's own use of mate retention behavior, however, (c) there was a dissimilarity effect for predicting mate retention behaviors. Specifically, participants who were less physically attractive and were in romantic relationships with physically attractive partners employed more intrasexual retention tactics.